Hsp90β inhibition upregulates interferon response and enhances immune checkpoint blockade therapy in murine tumors - Rahmy, Sharif; Mishra, Sanket J.; Murphy, Sean; Blagg, Brian S. J.; Lu, Xin (Frontiers in Immunology, 2022)
Response resistance to the immune checkpoint blockade (ICB) immunotherapy remains a major clinical challenge that may be overcome through the rational combination of ICB and specific targeted therapeutics. One emerging combination strategy is based on sensitizing ICB-refractory tumors with antagonists of 90kD heat shock protein (Hsp90) that target all four isoforms. However, pan-Hsp90 inhibitors are limited by the modest efficacy, on-target and off-tumor toxicities, and induction of the heat shock response (HSR) that overrides the effect of Hsp90 inhibition. Recently, we developed Hsp90β-selective inhibitors that were cytotoxic to cancer cells but did not induce HSR in vitro. Here, we report that the Hsp90β inhibitor NDNB1182 downregulated CDK4 (an Hsp90β-dependent client protein) and induced the expression of endogenous retroviral elements and interferon-stimulated genes. In syngeneic mouse models of prostate cancer and breast cancer, NDNB1182 significantly augmented the efficacy of ICB therapy. Furthermore, NDNB1182 showed superior tolerability to the pan-Hsp90 inhibitor Ganetespib in mice. Our findings provide evidence that Hsp90β inhibition is a potentially effective and safe regimen to combine with ICB to treat immunotherapy-refractory solid tumors.